Do you always choose what you like? Subtle social cues increase preference-choice consistency among Japanese but not among Americans - Uchida, Yukiko (2017)
Previous research has suggested that stability of self-concept differs across cultures: in North American cultural contexts, people’s self-concept is stable across social contexts, whereas in Japan, different self-concepts are activated within specific social contexts. We examined the implications of this cultural difference for preference-choice consistency, which is people’s tendency to make choices that are consistent with their preferences. We found that Japanese were less likely than Americans to choose items that they liked the most, showing preference-choice inconsistency. We also investigated the conditions in which Japanese might exhibit greater preference-choice consistency. Consistent with research showing that in Japanese culture, the self is primarily conceptualized and activated by social contexts, we found that subtle social cues (e.g., schematic representations of human faces) increased preference-choice consistency among Japanese, but not among Americans. These findings highlight that choices do not reveal preferences to the same extent in all cultures, and that the extent to which choices reveal preferences depends on the social context.